NPM1 functions in epitranscriptomics - Zhou, Fengbiao; Müller-Tidow, Carsten (Nature genetics, 2019)
A new study identifies germline NPM1 mutations in people with dyskeratosis congenita. These NPM1 mutations inhibit ribosomal RNA 2´-O-methylation by decreasing the binding of the rRNA methyltransferase FBL to small nucleolar RNAs. Thus, NPM1 influences ribosomal functions via epitranscriptomic regulation.